Meningkatkan Motivasi Belajar Peserta Didik Kelas V pada Mata Pelajaran IPAS Menggunakan Media Interaktif Wordwall dan Video Animasi Di SDN 34 Mataram - Aprilia, Bq. Novi; Setiadi, Dadi; Fitriyani (Mataram University, 2025)
This study aims to enhance the learning motivation of fifth-grade students in the IPAS subject through the use of interactive media, specifically Wordwall and animated videos, at SDN 34 Mataram. The research employs a Classroom Action Research (CAR) design conducted in two cycles. The instruments used include a learning motivation questionnaire and an observation sheet. The research subjects consisted of 20 fifth-grade students with diverse motivational characteristics. Data were analyzed using quantitative techniques. The results indicate an overall increase in students’ learning motivation in the IPAS subject. This improvement is evident from the initial diagnostic assessment, which showed that most students demonstrated low learning motivation, with 55% in the low category, 25% in the medium category, and 10% each in the high and very high categories. After the implementation of Wordwall interactive media and animated videos in Cycle I, student motivation increased, with 25% in the very high category, 35% in the high category, 30% in the medium category, and only 10% in the low category. In Cycle II, even more positive results were obtained: 40% of students were in the very high category, 50% in the high category, and 10% in the medium category, with no students categorized as low or very low. These findings demonstrate that the use of Wordwall interactive media and animated videos can significantly improve students’ learning motivation.